2014
DOI: 10.1021/ie500235f
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Integrated Pressure-Swing-Distillation Process for Separation of Tetrahydrofuran/Methanol with Different Feed Compositions

Abstract: A process optimization is carried out to separate binary azeotropic mixtures of tetrahydrofuran and methanol by pressure-swing distillation according to the pressure-sensitive property of the binary system. Rigorous steady-state simulation that is based on the minimization of the total annual cost for partially and fully heat-integrated pressure-swing-distillation processes is implemented on Aspen Plus following the sequential iterative optimization procedure. The feasible sequence of high pressure and low pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…There has been much interest in investigating the heat integration used for PSD processes in recent years. Heat integration PSD (HIPSD) can occur in one of two ways, either by integrating the condenser in the high pressure column (HPC) with the reboiler in the low pressure column (LPC) (condenser/reboiler type) or by integrating the stripping section in the LPC with the rectifying section in the HPC (rectifying/stripping type) (Sorensen, 2001;Suphanit, 2011;Wang et al, 2014). Both schemes have significant advantages in energy saving.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much interest in investigating the heat integration used for PSD processes in recent years. Heat integration PSD (HIPSD) can occur in one of two ways, either by integrating the condenser in the high pressure column (HPC) with the reboiler in the low pressure column (LPC) (condenser/reboiler type) or by integrating the stripping section in the LPC with the rectifying section in the HPC (rectifying/stripping type) (Sorensen, 2001;Suphanit, 2011;Wang et al, 2014). Both schemes have significant advantages in energy saving.…”
Section: Introductionmentioning
confidence: 99%
“…[12] The results showed that the PSD process had greater reduction on total annual cost compared with the traditional distillation process. In addition, the PSD can also be used to deal with the homogeneous azeotropic mixture in the RD process.…”
Section: Introductionmentioning
confidence: 97%
“…The influence of pressure on azeotropic composition and azeotropic temperature for binary system is always used to prove pressure-sensitivity [39][40][41] which is one of decisive factors for PSD, and triangular diagrams including residue curve maps (RCMs) [5,38,[42][43][44][45][46] are usually used to analyze the feasibility of multicomponent separation. Fien and Liu [47] reviewed the design of separation processes and illustrated the use of ternary diagrams including RCMs for the feasibility analysis, flowsheet development, and preliminary design.…”
Section: Introductionmentioning
confidence: 99%